2011
DOI: 10.1262/jrd.10-185m
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and In Vitro Culture of Male Germ Cells from Developing Bovine Testis

Abstract: Abstract. The transition from male primitive germ cells (gonocytes) to type A spermatogonia in the neonatal testis is the initial process and a crucial process in spermatogenesis. However, in large domestic animals, the physiological and biochemical characteristics of germ cells during the developmental processes remain largely unknown. In this study, we characterized bovine germ cells in the developing testis from the neonatal stage to the adult stage. The binding of the lectin Dolichos biflorus agglutinin (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 51 publications
5
72
0
3
Order By: Relevance
“…3) suggests that proper stimulation of somatic cells, including Leydig cells, Sertoli cells and endothelial cells (which are necessary for the survival and proliferation of germ cells; Aponte et al 2008), supports the colony formation of gonocytes on the DBA-precoated plates. In fact, the colony formation of bovine gonocytes can be supported on GN-coated plates for the first week of culture (Fujihara et al 2011). However, adhesion affinity and colony formation of gonocytes were lower on GN-compared with DBA-precoated plates (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…3) suggests that proper stimulation of somatic cells, including Leydig cells, Sertoli cells and endothelial cells (which are necessary for the survival and proliferation of germ cells; Aponte et al 2008), supports the colony formation of gonocytes on the DBA-precoated plates. In fact, the colony formation of bovine gonocytes can be supported on GN-coated plates for the first week of culture (Fujihara et al 2011). However, adhesion affinity and colony formation of gonocytes were lower on GN-compared with DBA-precoated plates (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Colonies of bovine gonocytes have stem cell potential, as identified by the expression of stem cell-specific genes (NANOG and POU5F1; Fujihara et al 2011). The colony formation of testicular cells in culture depends on the presence of germ cell populations (Aponte et al 2008), and these cell populations were strongly associated with the expression of NANOG and POU5F1 (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Certain rodent markers for germ cells and SSCs such as VASA, DAZL, PLZF, and GFR1are also of monkey (Hermann et al, 2007) and in other species. VASA expression marks spermatogonia in sheep (Borjigin et al, 2010), buffalo (Goel et al, 2010b) and bull (Fujihara et al, 2011) testis. It has been demonstrated that GFR1 is a marker for mouse SSCs and probably their progeny (Meng et al, 2000;Buageaw et al, 2005;Hofmann et al, 2005;Naughton et al, 2006;He et al, 2007), and that KIT is a characteristic for the more differentiated spermatogonia, including type A 1-4 spermatogonia (Yoshinaga et al, 1991).…”
Section: Markers Of Sscsmentioning
confidence: 99%